The Relationship Between Psychological Well-Being with Celebrity Worship in K-Pop Fans using Twitter - Parawangsah, Khoviva Indah; Hasanah, Muhimmatul; Sholichah, Ima Fitri (Journal Universitas Muhammadiyah Gresik Engineering, Social Science, and Health International Conference (UMGESHIC), 2023)
This study aims to determine the relationship between psychological well-being and celebrity worship among K-pop fans who use Twitter. This research method is quantitative. The population in this study are K-Pop fans who use Twitter, both women and men. As well as determining the sample using purposive sampling technique. The research data was collected by distributing the Google Form link with the Psychological Well-being and Celebrity Worship scales. The scale used in this research is a Likert scale with 5 answer choices for the Psychological Well-being scale and 4 answer choices for the Celebrity Worship scale. The measuring instrument used in this study for psychological well-being uses adaptations from Rachmayani and Ramdhani (2014) and the Celebrity Worship scale the researchers made themselves based on aspects belonging to Maltby et al (2006). Test the validity of the scale using content validity. Reliability test using Alpha Cronbach. The technique used in this study is to use correlation analysis techniques. The results of Spearman Rho correlation data analysis showed that the Rho value was -0.013 with p = 0.783 at sig. (2-tailed) is greater than 0.05 (p > 0.05). It can be concluded that there is no significant relationship between Psychological Well-being and Celebrity Worship.